Handbook of research on multidisciplinary approaches to entrepreneurship, innovation, and ICTs - Carvalho, Luísa Cagica, 1970-; Reis, Leonilde, 1962-; Prata, Alcina, 1969- (IGI Global, 2020)
"This book discusses the digitalization techniques of the modern workforce as well as important tools empowering social entrepreneurship initiatives"--